Pectin nanocoating of titanium implant surfaces ‐ an experimental study in rabbits. Issue 3 (14th March 2016) - Gurzawska, Katarzyna; Dirscherl, Kai; Jørgensen, Bodil; Berglundh, Tord; Jørgensen, Niklas Rye; Gotfredsen, Klaus
Abstract: Introduction: A major determinant of successful osseointegration of endosseous implants is the surface of the implant, which influences the cellular response of the surrounding tissues. A new strategy to improve osseointegration and bone healing is biochemical stimulation by surface nanocoatings that may increase adhesion of bone proteins, and bone cells at the implant surface. Nanocoating with pectins, plant cell wall‐derived polysaccharides, is frequently done using rhamnogalacturonan‐I (RG‐I). Aim: The aim of the study was to evaluate the effect of nanocoating titanium implants with plant cell wall‐derived rhamnogalacturonan‐I, on bone healing and osseointegration. Material and methods: Machined titanium implants were coated with three modifications of rhamnogalacturonan‐I (RG‐I). Chemical and physical surface properties were examined before insertion of nanocoated implants ( n = 96) into the left and right tibia of rabbits. Machined titanium implants without RG‐I nanocoating were used as controls ( n = 32). Total number of 128 implants was placed in tibias of 16 rabbits. Fluorochrome bone labels, calcein green and alizarin red S were given intravenously after 9 and 12 days, respectively. The bone response to the nanocoated implants was analyzed qualitatively and quantitatively after 2, 4, 6, and 8 weeks of healing using light microscopy and histomorphometric methods. Results: The RG‐I coating influenced the surface chemical composition; wettability and roughness, making the surface more hydrophilic without any major effect on surface micro roughness compared to control implant surfaces. The different modifications of pectin RG‐I did not significantly enhance bone healing and osseointegration analyzed after 2, 4, 6, and 8 weeks of healing compared to control implants. Although the qualitative analyses of the fluorochromes indicated a higher activity of bone formation in the mineralization front at the early stage, after 9 and 12 days at the RG‐I nanocoated implants compared to the control implants although no significant quantitative difference was demonstrated. Conclusion: The present study showed that nanocoating of titanium implants with pectin RG‐Is did not significantly enhance bone healing and osseointegration when placed in rabbit tibia bone.